2018
DOI: 10.1104/pp.18.00712
|View full text |Cite
|
Sign up to set email alerts
|

Growth at Elevated CO2 Requires Acclimation of the Respiratory Chain to Support Photosynthesis

Abstract: Plants will experience an elevated atmospheric concentration of CO (ECO) in the future. Growth of tobacco () at ECO more than doubled the leaf protein amount of alternative oxidase (AOX), a non-energy-conserving component of mitochondrial respiration. To test the functional significance of this AOX increase, wild-type tobacco was compared with AOX knockdown and overexpression lines, following growth at ambient CO or ECO The ECO-grown AOX knockdowns had a reduced capacity for triose phosphate use (TPU) during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 98 publications
3
27
1
Order By: Relevance
“…AA, MYXO and OLIGO are respiratory inhibitors, each with a well‐established site of action in the mitochondrion (Soole and Menz ). However, it is also well established that photosynthetic metabolism in the chloroplast depends upon extensive interactions with respiratory metabolism in the mitochondrion (Hoefnagel et al , Raghavendra and Padmasree , Sweetlove et al , Tcherkez et al , Gandin et al , Gardeström and Igamberdiev , Dahal et al , Dahal and Vanlerberghe , ). In this case, one might expect that a disruption of mitochondrial function might also perturb chloroplast function, at least in the light, and hence potentially engage retrograde signals from both organelles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AA, MYXO and OLIGO are respiratory inhibitors, each with a well‐established site of action in the mitochondrion (Soole and Menz ). However, it is also well established that photosynthetic metabolism in the chloroplast depends upon extensive interactions with respiratory metabolism in the mitochondrion (Hoefnagel et al , Raghavendra and Padmasree , Sweetlove et al , Tcherkez et al , Gandin et al , Gardeström and Igamberdiev , Dahal et al , Dahal and Vanlerberghe , ). In this case, one might expect that a disruption of mitochondrial function might also perturb chloroplast function, at least in the light, and hence potentially engage retrograde signals from both organelles.…”
Section: Discussionmentioning
confidence: 99%
“…This could confound the identification of mitochondrial retrograde signal(s) and signal transduction proteins. A related complication is that important metabolic interactions must occur between photosynthesis and respiration in the light (Hoefnagel et al , Raghavendra and Padmasree , Sweetlove et al , Tcherkez et al , Gandin et al , Gardeström and Igamberdiev , Dahal et al , Dahal and Vanlerberghe , ). Thus, disruption of mitochondrial function by inhibitors or mutants may indirectly alter energy metabolism in the chloroplast, resulting in the generation of additional chloroplast‐derived retrograde signals.…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive review of several crop species, Ainsworth and Long (2005) reported that the predicted rise in atmospheric CO 2 concentrations will benefit most C 3 plants. Elevated CO 2 is expected to stimulate photosynthesis and enhance light use efficiency into biomass and crop yield as well as improve water use efficiency (WUE) through closing stomata and preventing transpirational water loss (Ainsworth and Rogers, 2007; Dahal et al, 2014b; Dahal and Vanlerberghe, 2018a). Short-term exposure of C 3 plants from ambient to elevated CO 2 immediately stimulate the rates of photosynthesis (Cheng et al, 1998; Long et al, 2004; Ainsworth and Rogers, 2007; Dahal et al, 2012).…”
Section: Rising Atmospheric Co2mentioning
confidence: 99%
“…Plants were irrigated every other day and fertilized every 2 weeks with a 20-20-20 fertilizer containing 5.9% of nitrate nitrogen. The transgenic lines used in this study have been characterized earlier (Amirsadeghi et al, 2006;Wang et al, 2011;Wang and Vanlerberghe, 2013;Dahal and Vanlerberghe, 2018a). Amongst these, RI29 is the most effective knockdown (no detectable leaf AOX protein), while faint amounts of leaf AOX protein can still sometimes be detected in RI9.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%